ChemInform Abstract: TBHP/TEMPO‐Mediated Oxidative Synthesis of Imides from Amides. Issue 39 (September 2015) - Yu, Hui; Chen, Yuegang; Zhang, Yonghao
Abstract Various imides are efficiently synthesized by simple oxidation of appropriate amides under mild conditions using tBu‐OOH as the oxidant, CuBr as the catalyst, and TEMPO as the additive.